Penanganan limbah cair hasil pengolahan ikan asin dengan menggunakan metode ozonisasi - Widya Pangestika; Arif Baswantara; Nusaibah Nusaibah; David Indra Widianto; Arpan Nasri Siregar; Eneng Wulan Rahmawati (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Pangandaran Regency is famous for salted fish, both for consumption by the surrounding community and for souvenirs. In the salty fish production process, of course, a lot of liquid waste is produced. The method of preparation, washing and soaking are the three stages that make the most wastewater in salting fish. Salted fish processing liquid waste is an organic waste that can be reduced its pollution parameters through ozonation technology. This study aims to study the effect of effluent pH and ozonation time on the level of degradation of effluent pollution parameters, such as: TSS, TDS, COD, BOD5, and salinity. From the analysis results, it is known that the process of flowing ozone for 80 minutes at pH 9 can reduce TSS, TDS, and salinity to the maximum, by 86.23%, 62.42%, and 61.38%, respectively. The most reductions in COD and BOD5 were achieved after giving ozone for 20 minutes at pH 10, as much as 52.20% and 54.69%, respectively. It is known that the TSS and TDS of wastewater that has been given ozone may be below the quality standard set by the Minister of the Environment, but this does not yet apply to levels of COD and BOD5. Additional processing is required so that the COD and BOD5 values can be below the quality standards recommended by the Minister of the Environment.